(untitled) (Latakia University Journal -Biological Sciences Series, 2024)
This research aimed to study biological indicators and prepare a life table for the parasitoid S. cyanea at Different temperatures (20, 25, and 30 °C) and relative humidity (65±5%) and an illumination period of (8:16 hours) (light:dark). The biological indicators of the parasitoid S.caerulea were calculated using the (TWOSEX-MS Chart) program. The results showed that the highest The value of the Net reproductive rate (R0) was 5.73 at a temperature of 30°C, the final rate of increase (λ) was 1.04 at a temperature of 25° C, and the shortest generation period (T) was 35.22 days at a temperature of 30° C. The highest Fecundity (F) value for the Citrus wax scale was 11.6 at a temperature of 25° C. The emergence of adults and the survival rate was highest at 30 °C, where the adult female stage reached 52% and the adult male stage reached 58%.